Genomic analysis of Paenibacillus larvae isolates from the Czech Republic and the neighbouring regions of Slovakia - Matiašovic, Ján; Bzdil, Jaroslav; Papežíková, Ivana; Čejková, Darina; Vasina, Evgeniya; Bizos, Jiří; Navrátil, Stanislav; Šedivá, Mária; Klaudiny, Jaroslav; Pikula, Jiří (Research in veterinary science, 2023)
Paenibacillus larvae is the causative agent of American foulbrood (AFB), a devastating disease of honeybee larvae. In the Czech Republic, two large infested regions were recognised. This study aimed to analyse P. larvae strains occurring in the Czech Republic in the years 2016-2017 and to characterise the genetic structure of their population with the use of Enterobacterial Repetitive Intergenic Consensus genotyping (ERIC), multilocus sequence typing (MLST) and whole genome sequence (WGS) analysis. The results were complemented by the analysis of isolates collected in the year 2018 in areas of Slovakia located near the Czechia-Slovakia border. ERIC genotyping revealed that 78.9% of tested isolates belonged to the ERIC II genotype and 21.1% to ERIC I genotype. MLST showed six sequence types with ST10 and ST11 being the most frequent among isolates. Within six isolates we found discrepancies in correlations between MLST and ERIC genotypes. The use of MLST and WGS analysis of isolates revealed that each of the large infested geographic regions had its own dominating P. larvae strains. We assume that these strains represented primary sources of infection in the affected areas. In addition, the sporadic presence of strains identified by core genome analysis as genetically related was unveiled in geographically distant regions suggesting possible human-mediated transmission of AFB.
Keywords: Genotyping; Animals; Genotype; Honeybee; American foulbrood; Paenibacillus larvae; Genomics; Slovakia; lidé; genotyp; multilokusová sekvenční typizace; Epidemiology; AFB spread; Spojené státy americké; larva; Czech Republic; Bees; United States; Česká republika; Multilocus Sequence Typing; včely; Slovenská republika; Larva; zvířata; genomika; Humans